Clinical evaluation of combination therapy with flomoxef and aztreonam for infections associated with hematological disorders - Fukuda Masataka; Hirashima Kunitake (CHEMOTHERAPY, 1994)
Flomoxef (FMOX) and aztreonam (AZT) were used concurrently to treat infections complicated by hematic disease. A total for 102 subjects were evaluated, and the total efficacy rate including “remarkably effective” and “effective” was 69.6%. Acute leukemia was found in the largest number of patients, 49, followed by 14 cases of malignant lymphoma and 10 cases of chronic myelogenous leukemia. By type of infection, patients suspected of having sepsis were the largest in number, being 78, and the efficacy rate was 69.2%. The efficacy rates for sepsis and pneumonia were 66.7%(6 cases) and 57.1%(7 cases), respectively. The efficacy rates by neutrophil count before administration of FMOX and AZT and at 7 days after administration were both 65.5% with doses less than 500/μl, both 53.8%with doses less than 100/μl and both 71.7% with doses more than 500/μl. The efficacy rate was 75.0% in the granulocyte colony stimulatirrg factor (G-CSF) concurrent use group and 68.3% in the non-concurrent use group. Patients whose neutrophil count before administration of the antibiotics was less than 100/μl included 5 cases of 8 (62.5%) in the concurrent use group and 7 cases of 14 (50.0%) in the nonconcurrent use group. As causal bacteria, Staphylococcus strain accounted for 45.5% of infections followed by Pseudomonas strain. The blood level of G-CSF reflected the severity of inflammation and was correlated with CRP. Concurrent treatment with FMOX and AZT exhibited a high level of safety in infections complicated by hematic disease and showed high efficacy rates. 血液疾患に併発した感染症に対して, flomoxef (FMOX)・aztreonam (AZT) の併用療法を行った。評価対象例は, 102例で著効, 有効を合わせた総有効率は, 69.6%であった。症例は急性白血病がもっとも多く49例で, 次いで悪性リンパ腫14例, 慢性骨髄性白血病10例等であった。感染症別では, 敗血症疑いの症例がもっとも多く78例でその有効率は, 69.2%であり, 敗血症では6例で66.7%, 肺炎では7例57.1%の有効率であった。FMOX・AZT投与前と投与開始後7日目の好中球数別有効率では, ともに500/μl以下では65.5%, ともに100/μl以下では53.8%で, ともに500/μl以上では71.7%であった。また, granulocyte colony stimulating factor (G-CSF) 併用群では, 有効率では, 75.0%であり, 非併用群では, 68.3%であり, 抗生剤投与前の好中球数100/μl以下の症例では, 併用群8例中5例 (62.5%), 非併用群14例中7例 (50.0%) であった。原因菌では, Staphylococcus属が45.5%を占め, 次いでPseudomonas属が多かった。また, G-CSFの血中濃度は炎症の重症度を反映しておりCRPと相関していた。FMOX・AZT併用療法は, 血液疾患併発感染症に対して安全性が高く, 有効率も高く有用であった。